Differentiation and plasticity of human vascular wall mesenchymal stem cells, dermal fibroblasts and myofibroblasts: a critical comparison including ultrastructural evaluation of osteogenic potential. (2nd November 2019) - Pasanisi, Emanuela; Ciavarella, Carmen; Valente, Sabrina; Ricci, Francesca; Pasquinelli, Gianandrea
ABSTRACT: Mesenchymal stem cells (MSCs) share many properties with other tissue stromal cells, including cell morphology, immunophenotype, differentiation and immunologic properties. In this study, we compared the immunophenotype and the differentiation potential of human vascular wall mesenchymal stem cells (hVW-MSCs) with those of human dermal fibroblasts and myofibroblasts. Cell morphology and surface markers were evaluated by immunofluorescence and flow cytometry; functional assays for immunomodulation, angiogenesis, adipogenesis and osteogenesis were performed, together with the mRNA analysis of the critical differentiation genes. hVW-MSCs, dermal fibroblasts and myofibroblasts were all negative to CD34, whereas the expression of CD44 stemness marker was more intense in hVW-MSCs. As expected, hVW-MSC plasticity was wide and the angiogenic, adipogenic, osteogenic features were confirmed. Fibroblasts were the less effective in terms of immunomodulation, angiogenesis and adipogenic differentiation; differently from fibroblasts, the myofibroblasts showed a poor angiogenic commitment. The mineralization assay was positive in all the three cell types, but ultrastructure interestingly evidenced differential osteogenic patterns among them. Our study supports the higher anti-inflammatory and wound healing repair features of hVW-MSCs, in comparison to the other stromal cells investigated. Moreover, we underline the importance of ultrastructure for investigating the specific osteogenic pattern for each cell type.